Syrjäseutukoulujen digitalisoituminen : opettajien kokemuksia muutoksen eturintamalta - Koittola, Olli (2024)
This master's thesis explores the experiences of teachers in rural schools regarding the impacts of digital transformation on their work. The emphasis of the thesis is particularly on teachers' experiences regarding the adoption and use of technology among them. The research is based on both previous research findings and new empirical interview data. The interview data was collected from 26 teachers in various rural schools. The central aim of the thesis is to understand how teachers' perceptions of technology and digitalization influence the renewal of teaching and the application of technology. Additionally, the thesis aims to identify the challenges and opportunities encountered by teachers in rural schools regarding the use of technology, thus complementing the gap observed in the existing research literature. A qualitative research method was chosen in the thesis to support the in-depth understanding of teachers' responses. Theme analysis was used in the analysis of the responses. The results of the analysis of the interview data highlight how technical support, peer support, and student assistance are crucial factors in the integration of technology. Technology was also found to increase motivation and creativity among teachers and students, although teachers' reluctance may hinder its adoption. The results strongly indicate that with teachers' positive attitudes and support, the integration of technology into the teaching of rural schools can be significantly promoted. Recommendations derived from the results emphasize educational policy measures, improvement of teacher training, and strengthening support services, which can contribute to more geographically equitable learning opportunities and enhance the quality of education.